Utilization of dietary carbohydrate in tinfoil barb (Barbonymus schwanenfeldii, Bleeker 1853) fry - Nafees, Mohamed Salihu Mohamed (2022)
An optimal inclusion of carbohydrates in aquafeeds exerts protein-sparing effect in many farmed fishes and improves their growth. Dietary starch facilitates pellet expansion during feed extrusion and enhances water stability of pellets due to binding capacity. Although freshwater omnivorous fish can better utilize carbohydrate, the efficiency varies with species, and dietary carbohydrate level, source, type and physical form. The present study was conducted to evaluate carbohydrate utilization ability of tinfoil barb fry through five separate feeding trials. Tinfoil barb is an indigenous carp species that has a great potential in aquaculture as a food and ornamental fish. All feeding trials were conducted in 100 L aquaria fitted with top mechanical filters. Fry were stocked at 20 fish per aquarium and fed to satiation twice a day for eight weeks. In the first trial, five isonitrogenous and isocaloric diets with graded levels of corn starch (15, 20, 25, 30 and 35 %) were fed to the fish to determine its optimum starch utilization level. The diets for subsequent feeding trials were prepared with selected native and pregelatinized starch sources, sugars and α-cellulose to substitute corn starch. The fish fed 20% corn starch exhibited highest (P<0.05) growth, and feed and protein efficiency. Third order polynomial regression analysis revealed the maximum growth at 19.25% corn starch. At this optimum level, native wheat, taro, tapioca, sago and corn starches had comparable impact on fish growth. However, fish fed taro had lower (P<0.05) feed and protein efficiency, and nutrient and energy retention than those fed corn. Dietary taro and wheat groups had a lower (P<0.05) midgut α-amylase activity than those fed tapioca. Compared to corn starch, dietary taro shrunk (P<0.05) the fish hepatocyte while wheat shrunk its nucleus. Meanwhile, fish fed native and pregelatinized corn, sago and tapioca starches exhibited similar growth, feed efficiency and nutrient retention despite interactive influence of starch source and form (P<0.05) on feed digestibility and physical properties. Among the different carbohydrate types, glucose caused poor performance in fish (P<0.05) than sucrose, maltose, dextrin and tapioca starch. Growth and midgut α-amylase activity of fish fed 19.25% dietary sucrose was higher (P<0.05) than those fed glucose and tapioca starch. Nevertheless, survival of fish fed tapioca was higher (P<0.05) after a 14-d challenge test with Aeromonas hydrophila than those fed sucrose and dextrin. When the starch content of tinfoil barb diet was substituted with 0, 3, 6, 9 and 12 % α-cellulose, fish growth remained unchanged while α-amylase activity, feed and protein efficiency and protein retention showed increasing trends with rising fiber level. However, based on the overall fish performances, it was concluded that tinfoil barb fry could better utilize native corn, sago and tapioca starches at 19.25% dietary inclusion level. As corn starch is an imported commodity in Malaysia and locally produced sago starch fetched high price, the use of native tapioca starch in tinfoil barb diet was recommended.